Missed Nursing Care in Hospitalized Patients - María Guadalupe Moreno-Monsiváis; Catalina Moreno-Rodríguez; Ma. Guadalupe Interial-Guzmán (Universidad de La Sabana, 2015)
Objective: Determine missed nursing care in hospitalized patients and the factors related to missed care, according to the perception of the nursing staff and the patient. Method: Correlational descriptive study of a sample of 160 nurses and hospitalized patients, using the MISSCARE Nursing Survey. Results: Nursing personnel indicated there were fewer care omissions in continuous evaluation interventions (M=94.56; SD=11.10). The greatest number of omissions pertained to basic care interventions (M=80.2; SD=19.40). Patients mentioned there were fewer omissions in continuous evaluation interventions (M=96.32; SD=7.96), while the greatest number of omissions pertained to patient discharge and education (M=45.00; SD=23.22). The factors that contributed to missed nursing care, according to the nursing staff, were related to human resources (M=80.67; SD=17.06) and material resources (M=69.72; SD=23.45); patients mentioned human resources and communication. Conclusions: Nursing care that is not carried out according to the needs of the patient, or is omitted or delayed, was identified. This aspect is relevant, since nursing care is fundamental to the recovery of hospitalized patients.   DOI: 10.5294/aqui.2015.15.3.2